2021
DOI: 10.1177/02557614211034189
|View full text |Cite
|
Sign up to set email alerts
|

The conservatory debated from a critical pedagogy perspective

Abstract: Spanish Conservatories of Music are educational institutions where, for the most part, the culture of Modernity is upheld and an aesthetic musical paradigm is enshrined. In this paper, therefore, it was important to reflect, firstly, on the teaching practices they implement and which have remained faithful to Positivist assertions, in the face of the different educational laws that have been passed. To this end, we carried out an analysis of the opinions of 20 students on a university Master’s course which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…In order to improve the level of classroom teaching, we constantly explore the teaching paradigm of education in modern local colleges and universities and constantly strive to improve the quality of talent cultivation. Literature [11] took all the students of a course in a Spanish conservatory as research subjects to interview surveys to collect their views using interpretive phenomenological analysis techniques. The results showed that the music students' recognition of critical pedagogy and openness to unknown educational methods and practices.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the level of classroom teaching, we constantly explore the teaching paradigm of education in modern local colleges and universities and constantly strive to improve the quality of talent cultivation. Literature [11] took all the students of a course in a Spanish conservatory as research subjects to interview surveys to collect their views using interpretive phenomenological analysis techniques. The results showed that the music students' recognition of critical pedagogy and openness to unknown educational methods and practices.…”
Section: Introductionmentioning
confidence: 99%
“…It can penetrate the mind and cultivate emotions; however, in the actual teaching process, students prefer music but are not interested in music lessons, and there are three main problems in music teaching in colleges and universities: monotony and mechanics of teaching methods, dullness and staleness of teaching process, specialization tendency of education, and the non-artistic tendency of education. These problems have led to students' gradual indifference and alienation from music classes [1][2][3]. Music teaching is an interaction between teaching and learning in which teachers use various teaching methods and approaches among teachers, students, and music to accomplish their teaching tasks.…”
Section: Introductionmentioning
confidence: 99%